Penerapan Asas Itikad Baik dalam Transaksi Jual-Beli Tanah (Studi Putusan Nomor 13/Pdt.G/2018/PN Bar) - Muhammad Asshidiq; Muhammad Farid Alwajdi (Ahmad Dahlan Legal Perspective, 2023)
The purpose of this study is to find out how the application of the principles of good faith in land transactions, and be more specific to analyze how the application of a good faith principle between the seller and the buyer on rule number 13/ PDT. G/2018/ pn bar.The method of research used was normative-law research, with law enforcement approaches and case approaches. The research uses primary and secondary and tesier legal sources. This study the authors concluded that in land transactions in case number 13/ PDT. G/2018/ pn bar raised the issue because one party had deviated from the principle of good faith in buying and selling, when one party of the agreement already applied its good faith in carrying out a covenant.